ULTRASTRUCTURAL REMODELING OF RAT SUBMANDIBULAR GLANDS IN CHRONIC ETHANOL INTOXICATION - Yeroshenko G.А.; Shevchenko, K.V.; Lisachenko, O.D.; Vilhova, O.V.; Yakushko, O.S.; Skotarenko, T.A.; Bilash, V.P. (World of Medicine and Biology, 2020)
The study presents a detailed analysis of the ultramicroscopic structure of the rat submandibular glands in chronic ethanol intoxication at the later stages of the experiment. It has been established that prolonged exposure to ethanol at the later stages of the experiment was characterized by the appearance of signs of adaptive-compensatory responses of the parenchymal elements and vessels of the blood microvascular system with the emergence of dystrophic changes and apoptosis of ductal epithelium; however, no complete regeneration of the structure was detected.